Size‐Dependent Control of Exciton–Polariton Interactions in WS2 Nanotubes. Issue 4 (12th December 2019) - Sinha, Sudarson S.; Zak, Alla; Rosentsveig, Rita; Pinkas, Iddo; Tenne, Reshef; Yadgarov, Lena
Abstract: Multiwall WS2 nanotubes (and fullerene‐like nanoparticles thereof) are currently synthesized in large amounts, reproducibly. Other than showing interesting mechanical and tribological properties, which offer them a myriad of applications, they are recently shown to exhibit remarkable optical and electrical properties, including quasi‐1D superconductivity, electroluminescence, and a strong bulk photovoltaic effect. Here, it is shown that, using a simple dispersion‐fractionation technique, one can control the diameter of the nanotubes and move from pure excitonic to polaritonic features. While nanotubes of an average diameter >80 nm can support cavity modes and scatter light effectively via a strong coupling mechanism, the extinction of nanotubes with smaller diameter consists of pure absorption. The experimental work is complemented by finite‐difference time‐domain simulations, which shed new light on the cavity mode–exciton interaction in 2D materials. Furthermore, transient absorption experiments of the size‐fractionated nanotubes fully confirm the steady‐state observations. Moreover, it is shown that the tools developed here are useful for size control of the nanotubes, e.g., in manufacturing environment. The tunability of the light–matter interaction of such nanotubes offers them intriguing applications such as polaritonic devices, in photocatalysis, and for multispectral sensors. Abstract : Strong coupling between the excitons and optical cavity modes in WS2 nanotubes leads to formation of polaritonic states. Here, the nanotubes are separated into fractions with different diameters using centrifugation. Optical extinction measurements show that the polaritonic states exist in nanotubes with a diameter larger than 80 nm, while pure excitonic resonances are obtained for nanotube diameters of 60 nm and below.